OPTIMIZING THE VOCATIONAL EDUCATION SYSTEM: CONTEMPORARY APPROACHES AND PROSPECTS - Hasan Yoqubovich Qalanov; Baxodirjon Sabirovich Nuridinov (Modern American Journals, 2025)
The article analyzes the issues of aligning the vocational education system with the requirements of the modern labor market. It presents the theoretical and practical foundations for optimizing the content of vocational education, the dual education model, the competence-based approach, and the importance of implementing digital technologies. Based on the study, a set of comprehensive recommendations aimed at improving the vocational education system has been developed.
Keywords: vocational education, optimization, dual education, competence, digital technologies, labor market, workforce training, Industry 4.0, innovative pedagogy.